PRICE TRANSMISSION IN SERBIAN MILK COMMODITY CHAIN - Popović, Rade; Radovanov, Boris (Economics of Agriculture, 2010)
This paper explores price transmission at Serbian dairy market for period 2007-2009. It analyzes milk price transmission on formal milk market for three products: pasteurized milk, white yoghurt and cheese. From processed raw milk in dairy plants 17% is turned in pasteurized milk, 35% in fermented liquid milk products and 31% in cheese and other non-liquid milk products (Popovic, 2009). Monthly data are collected from three levels of milk chain: farm level, processors and retailers. Three step approach based on: intensity, asymmetry and time lags in price transmission was applied. Distinction of two market levels was made, first between farmers and processors and second among processors and retailers. Additionally price transmission from world to nationally market was examined.